Foraging energetics of the Magellanic penguin Spheniscus magellanicus: a first case study in the subantarctic environment - Harris, Sabrina; Raya Rey, Andrea Nélida; Rey Faura, Daniel; Pütz, Klemens
Animals’ use of the space is the result of a complex decision-making process since the energetic efficiency while foraging is ultimately linked to individuals’ fitness and population dynamics. In penguins, foraging behavior is shaped by changes in the environment and, therefore, is a good indicator of the health of the southern oceans. Recent studies have validated the use of accelerometer data combined with GPS tracks to investigate the energy expenditure of penguins in the environment surrounding the colony. Fil: Harris, Sabrina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Raya Rey, Andrea Nélida. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Rey Faura, Daniel. Imbrsea; Bélgica Fil: Pütz, Klemens. Antarctic Research Trust;